Transport integration as the development trend’s of the Eurasian Economic Union (International relations and international law Journal, 2018)
The article discusses the development of transport integration of the Eurasian Economic Union, shows the growing role of the EEU in the political, economic and military spheres, depending on the strengthening of transport corridors. The transport and logistics potential of the Eurasian Economic Union and its development opportunities go far beyond the integration group of states. The authors analyze the key factors, depending on which transport integration develops in the Eurasian space; attention is given to the priorities of the development of the Eurasian transport potential. One of the world’s largest transportation systems is being created within the framework of the EEU. «Eurasian transcontinental corridor», the new high-speed transport of mixed transport should become a key element of the revived Silk Road. This project includes a new economic policy «Nurly Zhol» (Path to the Future), as announced by the President of Kazakhstan Nursultan Nazarbayev. In the future, a new regional integration bloc will be created, which will include other countries of the Eurasian continent, first of all, the partners of the EEC and China in the SCO. The creation of transcontinental logistics corridors is a strategic task for many centers of power in Eurasian. If by 2025 the process of formation of the Unified Transport Policy is completed, if all existing obstacles are removed for transportation by any means of transport, then the EEU transport systems will reach a new level of functioning, which in fact will indicate their integration. Within the framework of the EEU, efforts are being made to coordinate the transport development strategies of the participating states.Key words: transport integration, transit, transport corridor, common transport space.